Effectiveness of Self-Management Related to Physical Activity with Life Quality in Hypertension - Juliyanti Cardoso Amaral; Shanti Wardaningsih; Lisa Musharyanti (Universitas STRADA Indonesia, 2025)
Background: Hypertension is a major cause of disability and death worldwide. Efforts to reduce blood pressure and disease complications can be made by changing lifestyle, controlling the disease, and monitoring blood pressure regularly. Blood pressure management and improved quality of life can be achieved through effective self-management, particularly through physical activity. Purpose: The purpose of this literature review is to identify the effectiveness of self-management in physical activity in improving the quality of life of patients with hypertension. Methods: In this study, three international databases, i.e., Dimensions, Scopus, and ScienceDirect, were included. There were initial 605 articles from the last 5 years (2020 to 2024). The inclusion criteria used included English articles, original articles, and full text. Then, after screening using the Prisma guide, 18 articles met the criteria. Results: The literature review showed that quality of life, physical activity and self-management in patients with hypertension can be improved with digital interventions, support from various parties (family and society, multidisciplinary health workers), and self-management training. There is evidence that exercise such as walking, aerobic exercise, and light strength training can lower blood pressure and improve health status. Social and psychological support are also critical in supporting self-management. Conclusion: A comprehensive approach, which includes a combination of technology-based interventions, multidisciplinary support and self-management training in physical activity, is needed to improve the quality of life of patients with hypertension. Continuous intervention and support programs can encourage patients to adopt a healthy lifestyle and be motivated to control the disease.